2016
DOI: 10.3139/113.110459
|View full text |Cite
|
Sign up to set email alerts
|

Hygienic Performance of Commercial Dishwashers with Water-Change System – An Experimental Study

Abstract: Hygienic Performance of Commercial Dishwashers with Water-Change System -A nE x p er i m en t a lS t u d y Commercial dishwashers are used in community facilities such as hospitals, refectories, nursing homes or food services. In this area, kitchen and food hygiene is of great importance to ensure consumer health. The aim of this study was to verify the hygienic performance of commercial dishwashers with a water-change system by use of bioindicators. This test method is described in DIN SPEC 10534. Micrococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Noting that bacteria such as E. faecium are not easily exterminated by the high temperatures prevailing within the dishwasher during and after the rinse cycle, Ståhl Wernersson and co-authors in [78] stressed the need to ensure that dishwashers are able to provide a high degree of mechanical cleaning, which reportedly has a negative correlation to the yeast colonies detected in dishwashers [52]. Kerschgens and colleagues [82], in hygienic performance tests carried out with M. Luteus, found that higher washing temperatures were more successful in reducing viable cell count than higher rinsing temperatures.…”
Section: Use Phasementioning
confidence: 99%
“…Noting that bacteria such as E. faecium are not easily exterminated by the high temperatures prevailing within the dishwasher during and after the rinse cycle, Ståhl Wernersson and co-authors in [78] stressed the need to ensure that dishwashers are able to provide a high degree of mechanical cleaning, which reportedly has a negative correlation to the yeast colonies detected in dishwashers [52]. Kerschgens and colleagues [82], in hygienic performance tests carried out with M. Luteus, found that higher washing temperatures were more successful in reducing viable cell count than higher rinsing temperatures.…”
Section: Use Phasementioning
confidence: 99%
“…Three papers are concerned with hygiene issues during laundering. Bockmühl et al characterized the microbial communities in household washing machines [5], Stamminger et al investigated the hygienic performance of commercial dishwashers [7] and Wasilewski et al studied the impact of hop cone extracts on the antibacterial properties of toilet cleaners [11].…”
mentioning
confidence: 99%
“…Much attention was also devoted to performance and consumption of washing machines in Europe [8], the microbial communities in household washing machines [2] and dishwashers [7], the hygiene in commercial dishwashers [14] and in domestic laundry [10], the consumer satisfaction with the performance of detergents [4] and the use of hop cone extracts in toilet cleaners [5].…”
mentioning
confidence: 99%
“…Four of the top 17 papers of 2016 were part of this special issue. The papers addressed the development of a real-time measurement using a novel and tailored QCM-D methodology for screening of detergent formulations [3], the water and energy consumption in domestic laundry [6], the interactions of protease and surfactants [9] and the effect of relevant detergent components on the cleaning performance in low temperature electric household dishwashing [13].Much attention was also devoted to performance and consumption of washing machines in Europe [8], the microbial communities in household washing machines [2] and dishwashers [7], the hygiene in commercial dishwashers [14] and in domestic laundry [10], the consumer satisfaction with the performance of detergents [4] and the use of hop cone extracts in toilet cleaners [5].Other topics attracting great interest in 2016 were those papers which reported on novel surfactants for formulations of cosmetics [1], the interactions of Gemini ester quats with biological membranes [12], an environmentally friendly inhibitor for scale in cooling water systems [11], and a terpolymer inhibitor for CaCO 3 and BaSO 4 in oil fields [17].Another topic receiving special attention was the behavior of surfactant mixtures such as carbamate surfactants with anionic surfactants [15] and of anionic Gemini surfactants with amphoteric surfactants [16]. …”
mentioning
confidence: 99%